Incorporation of Young Coconut (Cocos nucifera) Mesocarp Increases the Antioxidant Activity, Phenolic Compounds and Oxidative Stability of Cookies - Leliana, Lulum; Setyaningsih, Widiastuti; Palma, Miguel; Supriyadi, Supriyadi; Santoso, Umar (Trends in Sciences, 2023)
Young coconut mesocarp (YCM) contains considerable phenolic compounds that provide high antioxidant activity. However, the YCM is identified as an underutilized by-product in food industries. A novel functional food derived from YCM, viz., cookies, was proposed through this study to take advantage of the containing antioxidants. The cookies were prepared using regular flour (CR) or substituted with YCM powder at 8 (C8) or 16 % (C16). The macro components (carbohydrate, protein, fat and ash), in vitro antioxidant activities, and the level of individual phenolic compounds in the cookies were measured. The addition of YCM powder increased the crude fiber by up to 5 % and moisture content by about 2 - 3 %. Conversely, the fat level was lowered by 1 %. The in vitro antioxidant activities of cookies C8 and C16 were noticeably increased compared to the CR. The increase was attributable to the presence of phenolic compounds such as catechin and 3 caffeic acid derivatives, which were retained after the baking process. The addition of YCM changed the visual appearance by darkening the color of cookies which was indicated by lightness at 45.33 and 23.87; a* value was 17.30 and 18.97; b* value was 29.47 and 19.83; and chroma at 34.15 and 27.49, for C8 and C16, respectively. The addition of YCM also reduced the hardness due to the presence of moisture content in the incorporated cookies. Additionally, the addition of YCM was effective in prolonging shelf-life by increasing the oxidative stability of YCM-based cookies, indicated by the lower peroxide value (0.1 mEq O2·kg–1) after 4 months of storage compared to the regular cookies. YCM powder can be an alternative source of antioxidants, and it may be possible to include YCM powder in cookies and other pastries to increase their nutritional value and antioxidant activity to produce functional food. HIGHLIGHTS Young coconut mesocarp (YCM) was used as an ingredient to produce functional cookies and produce a higher fiber and ash but lower lipid and protein content compared to regular cookies The incorporation of YCM into the cookies increased the antioxidant activity and phenolic compounds in the cookies The addition of YCM prolongs the shelf-life of cookies compared to the reference cookies by lowering the fat content due to the high fiber and inhibiting the oxidation process due to the presence of catechin, chlorogenic and 3 caffeic acid derivatives GRAPHICAL ABSTRACT